PENGARUH KESIAPAN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA PADA PEMBELAJARAN KALKULUS - Harmini, Triana (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2017)
This study aims to determine whether or not a significant relationship between the readiness of learning and students' achievement in Calculus. This study was conducted in the odd semester of the academic year 2016/2017. The population in this study is the students of Informatics Engineering, University of Darussalam Gontor who took calculus course consisting of 50 people. Data collection in this research using questionnaire and documentation method.The research instruments used are questionnaire.  Techniques of analysis data  used are Product Moment correlation and simple linear regression analysis with prerequisite analyses those are normality and linearity test applied to know the influence of readiness study toward the students' achievement in Calculus course. The analysis result of Product Moment correlation show that the coefficient of readiness is 0.808 with significance score 0,00. This means that there is a positive and significant correlation between the readiness of learning and the students' achievement in the Calculus course. While the results of Linear Regression analysis shows that determination coefficient is 0.652. It means that the readiness of study gives an effect of 65,2% on the students' achievement in Calculus course.